Sero-positivity and associated risk factors for contagious bovine pleuropneumonia under two cattle production systems in North Central Nigeria (2015)
A cross-sectional survey of 765 cattle in 125 nomadic and 375 cattle in 125 sedentary herds was conducted to investigate prevalence and risk factors for contagious bovine pleuropneumonia (CBPP) in the two production systems of Niger State in North Central Nigeria, between January and August 2013. Data on herd characteristics were collected using structured questionnaires administered on herd owners. Serological analysis was conducted using competitive enzyme linked immunosorbent assay (c-ELISA) test. Descriptive, univariate, and multivariate statistical analyses were conducted with OpenEpi version 2.3.1 software. Statistical significance was held at P<0.05. CBPP sero-prevalence in nomadic cattle was 16.2 % (confidence interval (CI) 13.7–19.0) and 9.6 % (CI 6.9–12.9) in sedentary cattle. The overall cattle-level seroprevalence for two the cattle production systems was 14.0 % (CI 12.1–16.1). Age and agro-ecological zones were significantly (P<0.001 and P<0.001, respectively) associated with sero-positivity to Mmm in nomadic production. Agroecological zone C had the highest sero-prevalence (25.3 %, CI 20.2–31.0). No significant cattle factors were detected in sedentary production. Factors significantly associated with CBPP occurrence at herd-level were contacts with other herds during grazing (P<0.001) and at watering points (P<0.001). Others were introduction of new cattle into herd (P<0.001), outbreaks of CBPP in an area (P<0.001), socio-cultural factors of cattle gifts and dowry payment (P<0.001), herd composition of keeping cattle and small ruminants together (P<0.001), and long trekking during migrations (P=0.0009). This study had shown the burden of CBPP in the two production systems. Sero-diagnosis and risk factor identification should be institutionalized as elements of epidemiosurveillance and control strategies for CBPP, especially in resource-poor pastoralists’ settlements in Nigeria.